Observing the Effects of Shaping on Gas Adsorption in Metal‐Organic Frameworks. Issue 27 (22nd July 2016) - Chanut, Nicolas; Wiersum, Andrew D.; Lee, U‐Hwang; Hwang, Young Kyu; Ragon, Florence; Chevreau, Hubert; Bourrelly, Sandrine; Kuchta, Bogdan; Chang, Jong‐San; Serre, Christian; Llewellyn, Philip L.
Abstract : A series of four micro‐ or mesoporous metal‐organic frameworks [UiO‐66(Zr), UiO‐66(Zr)_NH2, MIL‐100(Fe), MIL‐127(Fe)] were synthesized in powder form and pelletized in the form of spheres by using a polyvinyl‐based binder. The effect of pelletization on the adsorption of a series of gasses (N2, CO, CO2, CH4, C2 H6, C3 H8, C3 H6, C4 H10 ) at 303 K was evidenced in the adsorption isotherms and the enthalpies of adsorption measured by using microcalorimetric analysis. As expected, uptakes of gas per gram of material were lower for the spheres than for the powder. However, taking into account the bulk density, this tendency was inverted, suggesting that the spherical materials are of distinct interest for gas‐based applications. Nevertheless, other effects including partial pore restriction and active site "protection" may equally be evidenced for some pelletized materials, suggesting that the polyvinyl binder may play a more complex role. Abstract : A series of four metal‐organic frameworks were synthesized as powders and spheres, and these were characterized by gas adsorption at 30 °C coupled with microcalorimetry. Whereas most variations were expected, interesting effects including partial pore restriction and active site "protection" were also evidenced for some shaped materials, suggesting that the binder may play a more complex role.